Pneumonia knowledge and care seeking behavior for children under-five years in Jigawa, Northwest Nigeria: a cross-sectional study - Ayobami A. Bakare; Ayobami A. Bakare; Carina King; Julius Salako; Damola Bakare; Obioma C. Uchendu; Obioma C. Uchendu; Rochelle Ann Burgess; Funmilayo Shittu; Agnese Iuliano; Adamu Isah; Tahlil Ahmed; et al. (Frontiers in Public Health, 2023)
BackgroundBetween 2013 and 2022, Nigeria did not meet globally defined targets for pneumonia control, despite some scale-up of vaccinations, oxygen and antibiotics. A deliberate focus on community-based programs is needed to improve coverage of protective, preventive and treatment interventions. We therefore aimed to describe caregiver knowledge and care seeking behaviour for childhood pneumonia, in a high child mortality setting in Nigeria, to inform the development of effective community-based interventions for pneumonia control.MethodsWe conducted a cross-sectional household survey in Kiyawa Local Government Area, Jigawa State, Nigeria between December 2019 and March 2020. We asked caregivers about their knowledge of pneumonia symptoms, prevention, risks, and treatment. A score of 1 was assigned for each correct response. We showed them videos of pneumonia specific symptoms and asked (1) if their child had any respiratory symptoms in the 2-weeks prior; (2) their subsequent care-seeking behaviour. Multivariate regressions explored socio-demographic and clinical factors associated with care seeking.ResultsWe surveyed 1,661 eligible women, with 2,828 children under-five. Only 4.9% of women could name both cough and difficulty/fast breathing as pneumonia symptoms, and the composite knowledge scores for pneumonia prevention, risks and treatment were low. Overall, 19.0% (536/2828) of children had a report of pneumonia specific symptoms in the prior two-weeks, and of these 32.3% (176/536) were taken for care. The odds of care seeking was higher among children: with fever (AOR:2:45 [95% CI: 1.38–4.34]); from wealthiest homes (AOR: 2:13 [95% CI: 1.03–4.38]) and whose mother first married at 20–26 years compared to 15–19 years (AOR: 5.15 [95% CI: 1.38–19.26]). Notably, the caregiver’s knowledge of pneumonia was not associated with care seeking.ConclusionWhile some socio-demographic factors were associated with care seeking for children with symptoms of Acute Respiratory Infection (ARI), caregiver’s knowledge of the disease was not. Therefore, when designing public health interventions to address child mortality, information-giving alone is likely to be insufficient.